Intergenerational Study of Parents and Children, 1962-1993: (Detroit) - Thornton, Arland ([Verlag nicht ermittelbar], 1993)
This data collection provides information on family formation and dissolution among young adults. Families who had given birth to their first, second, or fourth child in 1961 comprised the group of Detroit-area Caucasian couples who were interviewed and surveyed over the period 1962-1993. The resulting longitudinal study encompasses seven waves of data collected from mothers across the entire span of their offspring's childhood. Included are demographic, social, and economic information about the parental family, information about the attitudes, values, and behavior of both the mother and the father, and information about the mother's desires and expectations for her child's education, career attainments, and marriage. The collection also offers three waves of interview data collected from the children at ages 18 through 23. These data describe the young adults' attitudes and values, their expectations for school, work, marriage, and childbearing, and their perceptions of their parents' willingness to be of assistance to them. Life history calendar files for 1985 and 1993 detail the young adults' periods of cohabitation, marriage, separation, divorce, childbearing, living arrangements, education, paid employment, and military service.